Distinguishing Meristic and Morphometric Traits in Three Species of the Genus Acanthobrama from Iranian Inland Waters - Keivan Abbasi Ranjbar; Atta Mouludi-Saleh; Soheil Eagderi; Alinaghi Sarpanah (تاکسونومی و بیوسیستماتیک, 2018)
Abstract This study aimed to compare meristic and morphometric traits of three species of the genus Acanthobrama from Iranian inland waters collected during 2011-2017. A total 68 specimens of A. marmid from the Gamasiab River, Tigris river drainage, 85 specimens of A. microlepis from the Arasand Sefid rivers, Caspian Sea basin, and 90 specimens of A. urmianus from Mahabad-Chai and Godar-Chai rivers, Lake Urmia basin were captured by beach seine and electrofishing device. After anesthesia, the collected specimens were fixed into 10% buffered formalin and were transferred to the laboratory for further studies. Six meristic and 16 morphometric characters were counted and measured. The results showed a significant difference between the studied species in all morphometric traits except the pectoral fin length (P<0.05). In the cluster analysis, A. microlepis and A. urmianus were positioned in a clade. A significant difference found between the studied species in terms of the  meristic traits, including the lateral line scales, dorsal-fin unbranched and branched rays, and Anal-fin branched rays (P<0.05). MANOVA/CVA indicated that A. urmianus differed from A. microlepis in terms of the meristic traits. Also A. microlepis was positioned in a clade based on the result of meristic traits cluster analysis.